Self-Medication among Medical and Nonmedical Students at the University of Gondar, Northwest Ethiopia: A Cross-Sectional Study - Zelalem T. Tesfaye; Asrat E. Ergena; Bilal T. Yimer (Scientifica)
Despite having some benefits, self-medication increases risks such as unnecessary use of medication, extended duration of consumption, incorrect diagnosis, drug-drug interactions, and polypharmacy. Thus, the purpose of this study is to compare self-medication practice between medical and nonmedical students of the University of Gondar, Northwest Ethiopia. An institutional-based cross-sectional comparative study was conducted on medical and nonmedical students of the University of Gondar from March 25 to May 15, 2018. A comparative sample of 213 medical and 212 nonmedical students were enrolled in the study. Data were collected by physically visiting the students in their campuses, using a semistructured questionnaire. Of the participants with a history of medication use in the past 12 months, 64.5% practiced self-medication. The prevalence of self-medication was 59.7% among medical students and 69.0% among nonmedical students. “Knowing the treatment of the disease” was the most frequent reason behind self-medication. Analgesics/antipyretics were the most common categories of medications used, whereas headache was the predominant ailment for which the medications were used. Self-medication practice was found to be higher in the fifth year students and nonmedical students (p<0.05). In conclusion, self-medication is common among students of the University of Gondar. Nonmedical students were more likely to have practiced self-medication as compared to medical students.